1994
DOI: 10.1042/bj3030155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic incubation of CaCo-2 cells with eicosapentaenoic acid (20:5, n-3) and oleic acid (18:1, n-9) on triacylglycerol production

Abstract: CaCo-2 monolayers, cultured for 1 week after reaching confluence, were incubated with micellar solutions of fatty acids for up to 7 days. These conditioned cells were incubated acutely (5 h) with eicosapentaenoic acid and oleic acid, and the levels of cell-associated and secreted triacylglycerol were determined. With acute addition of oleic acid, both cell-associated and secreted triacylglycerol were decreased in cells chronically exposed to eicosapentaenoic acid. This effect was observed after as little as 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…We have shown that secretion of lipoproteins can be further modulated by OA supplementation to obtain secretion of small and large CM. In some studies, OA was delivered to Caco-2 cells as part of TC micelles (21,32,50,51). In these studies the concentrations of OA used were below Ϸ0.8 mM; a concentration that we found to be less than the optimum amount required for CM secretion (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that secretion of lipoproteins can be further modulated by OA supplementation to obtain secretion of small and large CM. In some studies, OA was delivered to Caco-2 cells as part of TC micelles (21,32,50,51). In these studies the concentrations of OA used were below Ϸ0.8 mM; a concentration that we found to be less than the optimum amount required for CM secretion (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Also, studies with Caco-2 cells have demonstrated that incubation with (n-3) VLCPUFAs lowered triglyceride synthesis and secretion (11)(12)(13)(14)(15). Finally, a single study with cultured intestinal biopsies obtained from malnourished patients demonstrated a decreased triglyceride resynthesis in cells from subjects that had consumed an (n-3) VLCPUFA supplemented diet for 2 weeks (30).…”
Section: Discussionmentioning
confidence: 95%
“…Altered enterocyte function and increased chylomicron clearance from plasma could contribute to the observed effects of fish oil (6,9,10). Some in vitro studies have suggested that (n-3) VLCPUFAs lower triglyceride resynthesis and chylomicron/ triglyceride secretion from enterocytes (11)(12)(13)(14)(15). However, chylomicron secretion appeared not to be decreased in rats fed (n-3) VLCPUFAs (8,16).…”
mentioning
confidence: 91%
“…However, the overall increased secretion could also result from either increased synthesis due to enhanced transcription or due to decreased posttranslational degradation. For example, the increase in apoB secretion following addition of oleic acid plus taurocholate [34] to Caco-2 cultures is not due to increased synthesis, but due to reduced degradation [11,13,46], while the increased apoB secretion following stimulation with transforming growth factor β has been shown to result from increased transcription of the apoB gene [41,50]. Further experiments are required to determine if reduced degradation and/or increased transcription is responsible for the increased apoB secretion due to growth of Caco-2 cells on HACT.…”
Section: Discussionmentioning
confidence: 99%